Functional and molecular diversity of rice straw decomposing bacteria and fungi - Do Thi, Xuan (2007)
The Mekong Delta is one of two rice baskets in Vietnam. Due to the convenient environmental conditions for rice cropping, people in this region have cultivated two or three rice crops a year. The intensive rice cultivation may have a negative impact on the soil environment and soil microbial diversity. To start investigations on how to reduce negative impacts on the soil environment and maintain the soil fertility in a long term perspective, this study was made. Rice stubble was collected from two different rice fields, Hoa An (Acid sulphate soil) and Vinh Nguon in the Mekong Delta. The functional traits and molecular diversity of cultivable bacteria and fungi as well as their effects on the next rice crop in terms of germination and radicle length were investigated. The effect of increasing number of species and functional groups was also studied to understand the relationship between microbial diversity and function. Microcosms containing sterile rice straw inoculated with taxonomically and functionally different microorganisms were used for this purpose.